Analysis of reinforced concrete structures through the ultrasonic pulse velocity: technological parameters involved - ADAMATTI,D.S. (2017)
Abstract The application of Nondestructive Testing methods (NDT) may be an interesting strategy to monitor the condition state of reinforced concrete structures, especially when there are problems related to mixing, conveying or placing the concrete. Among the NDT methods, the Ultrasonic Pulse Velocity (UPV) has been one of the most used in various fields of civil engineering, due to the ease of operation, low cost, test velocity and low level of damage to the surface analyzed. This work aims to study the influence of certain technological variables in the results obtained through UPV tests. With this aim two large blocks were cast at the laboratory, with dimensions close to real concrete elements. One of the elements was reinforcement with steel meshes on both sides while the other was cast without reinforcement. Inside these elements objects were introduced to reproduce internal concrete flaws. To facilitate the analysis the results were represented by means of a surface mapping image technique and were also subjected to statistical analysis. Through the study it was demonstrated that the correct choice of test parameters is crucial to obtain a right interpretation of UPV results from real structures.